UVC-LED assisted photo-Fenton/peroxydisulfate processes for microcontaminant and bacteria removal in a continuous flow reactor according to EU 2020/741 - Benzaquén, Tamara Belén (2024)
Bacteria inactivation (Escherichia coli (E. coli), total coliforms, Clostridium perfringens (C. perfringens)) and simultaneous removal of ubiquitous microcontaminants in actual municipal wastewater treatment plant secondary effluents was investigated at neutral pH using the UVC-LED assisted photo-Fenton reaction system operated in continuous flow. E. coli concentration ≤ 10 CFU/100 mL and 38 % microcontaminant removal was achieved in the reaction system at a hydraulic residence time of 30 min. UVC light alone and UVC light combined with an oxidant source (hydrogen peroxide, H2O2, or peroxydisulfate, S2O82−) were found to have a predominant effect on disinfection, meeting the EU 2020/741 validation (≥5 log10 reduction) and monitoring (≤10 CFU/100 mL) targets for both E. coli and C. perfringens after 30 min of treatment in batch mode. However, in the presence of either 0.05 or 0.1 mM of ferric nitrilotriacetate (Fe3+-NTA) the bacteria inactivation kinetics decreased due to reduced UVC light penetration along the water depth. In contrast, microcontaminant removal was accelerated using 0.05 or 0.1 mM of Fe3+-NTA and 1.47 mM H2O2. Overall, the results revealed that the treatment conditions favouring microcontaminant removal hindered disinfection and vice versa, and that the disinfection levels of C. perfringens (≤102 CFU/100 mL) reached in the batch mode experiments could not be attained under the continuous flow regime. This points out the need of performing disinfection experiments under continuous flow operation, as shown in the present study to determine the disinfection performance of UVC-LED assisted photo-Fenton reaction systems.